Analysis of the antihypertensive drugs prescription on the outpatient level - A. Yа. Bazylevych (Zaporožskij Medicinskij Žurnal)
Aim of the study was to explore the choice of antihypertensive drugs by doctors therapists of ambulatory and outpatient units based on medical and sociological research.